Digitalisasi UMKM Sebagai Upaya Pemberdayaan Dan Peningkatan Kesejahteraan Masyarakat Kecamatan Getasan, Kabupaten Semarang - Endang Suhendar; Ambar Tri Hapsari; Siti Suaedah; Diah Mariana; Atfal Murodif (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
This research aims to analyze the digitalization program in MSMEs as an effort to empower and improve the welfare of the people of Getasan District, Semarang Regency. This research uses a qualitative approach with a case study design. Using a marketing strategy for MSME products through digital marketing in Getasan District, Semarang Regency can be a strategic step to increase product visibility and sales. The implementation of marketing digitalization in Getasan District, Semarang Regency was carried out by introducing Instagram, Twitter, TikTok, Facebook, Shopee and Tokopedia. However, in its implementation there are still obstacles, namely limited internet access in Getasan District.